2023
DOI: 10.1177/15589250231181912
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic electrospinning for fabrication of poly(lactic acid)/graphite oxide/poly(dopamine) nanofiber membrane

Abstract: As a new preparation process of nanofibers, electrospinning technology developed by bionic spider spinning can further improve the molecular structure and mechanical properties of nanofibers, and obtain nanofibers and base membrane products with better mechanical properties. The spider spinning needs minimal energy consumption though it has a very long liquid transport tube. Because spider silk has high mechanical properties and wide industrial applications, so a kind of new biomimetic electrospinning technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…13 In particular, it has excellent mechanical properties that are unparalleled among industrial materials. 4,5 Therefore, spider silk is regarded as one of the future’s most promising industrial materials in the fiber industry. 68 Scientists have realized the potential for mass production of spider silk for commercial applications based on the favorable characteristics of spider silk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 In particular, it has excellent mechanical properties that are unparalleled among industrial materials. 4,5 Therefore, spider silk is regarded as one of the future’s most promising industrial materials in the fiber industry. 68 Scientists have realized the potential for mass production of spider silk for commercial applications based on the favorable characteristics of spider silk.…”
Section: Introductionmentioning
confidence: 99%
“…Tian et al imitated the spider’s long tube spinning 4,26,27 and combine it with electrospinning using the spinning mechanism of spider silk. 5,2830 Using low viscosity spinning solution of PVA, PAN and other high polymer as the object of this study, their research demonstrated that long tube spinning can alter the internal structure of nanofibers and influence of their properties (membranes). 31,32 Based on the research of Tian et al, this study examined the effect of various long needle length on the micro-morphology, mechanical properties, electrical properties, porosity, and hydrophobic properties of PVDF nanofiber membranes produced by electrospinning.…”
Section: Introductionmentioning
confidence: 99%